Ophthalmic administration of a 10-fold-lower dose of conventional nanoliposome formulations caused levels of intraocular pressure similar to those induced by marketed eye drops - Arroyo, C. M. (2018)
The purpose of this study was to compare the in vivo efficacy of several timolol (TM)-loaded liposomal formulations with current TM antiglaucoma treatment (aqueous 0.5% w/v eye drops). In this study, conventional liposomes (CL) and deformable liposomes, without (DL1) and with ethanol (DL2) were prepared and characterized. In addition, in vitro release and permeation studies, as well as in vivo lowering intraocular pressure (IOP) and biocompatibility studies were performed. It was found that the quali and quantitative lipid bilayer composition played a significant role in modifying the physical properties of vesicles. The deformability study and electronic microscopy images revealed that membrane elasticity of DL1 and DL2 was much higher than CL. However, in vitro permeation results showed that the flux and permeability coefficient were significantly higher in CL compared to DL. The IOP study revealed that TM-loaded CL showed the best pharmacological activity, in comparison to deformable vesicles. Compared to the eye drops, CL formulation could equally reduce the IOP but using a concentration 10-fold lower, whereas the effective time was significantly longer. In addition, the formulations showed no irritant effects after instillation on the ocular surface.